Resin-Build-Up as A Direct Monoblock Concept for Root Canal Dentin, Core, and Crown Restoration on Anterior Endodontically Treated Tooth - Kusumasari, Citra; Hatayama, Takashi; Tagami, Junji; Shimada, Yasushi, Prof. (UI Scholars Hub, 2024)
The long-term clinical performance of restoration in endodontically treated teeth (ETT) is an essential yet complicated strategy to achieve it. A resin-build-up tooth with higher elastic moduli is a minimally invasive strategy to decrease the risk of catastrophic root fracture. Additionally, intracanal resin composite anchorage simplifies the restorative procedure and increases the bonding. Objective: This case report describes a resin-build-up tooth restoration using the direct monoblock concept to replace a failed metal post and core and porcelain fused to metal (PFM) crown on the maxillary right central incisor. Case report: A 50-year-old man attended a dental university hospital with a chief complaint about the repeated detachment of the old resin-veneered crown along with the metal post on his maxillary right central incisor. He has been using that aged restoration for five years. The measurement of crown preparation in thickness was 2 mm, core length was 9 mm, post length was 7 mm, remaining gutta-percha was 5 mm, and the length from the end of gutta-percha to the apex was 1 mm. A Direct monoblock restoration using flowable and packable resin composite with universal adhesive was chosen to save time and to achieve long-term bonded restoration. Conclusion: Endodontically treated teeth on the maxillary incisor were successfully restored using the resin-build-up direct monoblock concept. The adhesive intracanal resin composite anchorage to a depth of 7 mm using a flowable resin composite replaced the post for ETT with favorable results. Moreover, the four-year follow-up of the clinical examination and evaluation showed good results.